Should Sinus of Valsalva be Replaced in Patients with Dilated Ascending Aorta and Aortic Valve Diseases? - Salihi,Salih (2018)
Abstract Introduction: The aim of this study is to investigate the change in the dimension of sinus of Valsalva in patients who underwent supracoronary ascending aorta replacement with aortic valve replacement. Methods: A total of 81 patients who underwent supracoronary ascending aorta replacement with aortic valve replacement were included. Ten of 81 patients died during the follow-up. The patients were divided into three groups according to the aortic valve diseases. Group I (n=17) included patients with bicuspid valves, group II (n=30) included patients with stenotic degenerative valves, and patients with aortic regurgitation constituted group III (n=24). In preoperative and follow-up periods, the sinus of Valsalva diameter of the patients was evaluated by echocardiographic examination. The mean age was 54.1±15.1 years. Twenty-eight (34.6%) patients were female and 12 (14.8%) patients were in New York Heart Association functional class III. Results: There was no early mortality. Late mortality was developed in 10 (12.4%) patients, 8 (9.9%) due to non-cardiac reasons. Late follow-up was obtained in 71 patients with a mean of 60±30.1 months postoperatively. During follow-up, the increase in the diameter of the sinus of Valsalva was significant in Group I (P<0.01), while in Group II and III it was insignificant (P>0.05). Conclusion: To avoid the risks associated with sinus of Valsalva dilatation, it is reasonable to replace the sinus of Valsalva in the setting of aortic valve replacement and ascending aorta replacement for bicuspid aortic valve with a dilated ascending aorta and relatively normal sinuses of Valsalva in young patients.